How does rest Interval duration affect performance? An experiment on high-intensity sprint exercises - İbrahim Orkun AKCAN; Cengiz ÖLMEZ (Baltic Journal of Health and Physical Activity)
Introduction: The purpose of this study was to examine the effects of interval and highintensity sprint training (RST) with different rest intervals on the respiratory function, aerobic and anaerobic power. (2) Materials and Methods: The study involved the voluntary participation of 20 male participants. The participants were divided into two groups: 2IRG (2-minute rest between repeated sprints) and 4IRG (4-minute rest between repeated sprints). The changes in the respiratory function, aerobic, and anaerobic power parameters were examined in the 2IRG and 4IRG athletes who performed two training sessions per week for 4 weeks. (3) Results: The findings indicated that there was no improvement in the respiratory function among the athletes, but there was a significant improvement in aerobic and anaerobic power parameters. However, this improvement was similar in both the 2IRG and 4IRG groups. (4) Conclusions: A 4-week high-intensity interval training program with two RST sessions per week was insufficient to elicit improvements in the respiratory function. However, RST protocols with 2-minute and 4-minute rest intervals provided similar aerobic and anaerobic benefits.